Management consulting today and tomorrow casebook : enhancing skills to become better professionals - Greiner, Larry; Olson, Thomas H.; Poulfelt, Flemming (Routledge, 2010)
Contains 20 cases, including those from Harvard and Stanford, that present the broad range of topics that are pertinent to the management consulting. This title helps to prepare consultants and other business managers for a successful future in a highly competitive consulting environment